The relationship between single nucleotide polymorphisms and skin cancer susceptibility: A systematic review and network meta-analysis - Zhang, Lu; Pozsgai, Éva; Song, Yongan; Macharia, John; Alfatafta, Huda; Zheng, Jia; Li, Zhaoyi; Liu, Hongbo; Kiss, István (Frontiers in Oncology, 2023)
Background: Single nucleotide polymorphisms (SNPs) interfere with the function of genes and then influence the probability of skin cancer. However, the correlation between SNPs and SC lacks statistical power. Hence, the purpose of this study is to compare the gene polymorphisms involved in skin cancer susceptibility by network meta-analysis, and to certain the relationship between SNPs and SC risk. Methods: PubMed, Embase and Web of Science were searched from 2005 to May 2022. NOS score was used for bias judgment. ORs and their 95% CI were employed for estimating heterogeneity within and between studies. Direct meta-analysis and network meta-analysis were carried out to identify SNPs related to SC. The P-score of each SNP was compared to get the rank probability. Subgroup analyses were also performed by tumour type. Results: 275 SNPs from 59 studies were included in this study. Two subgroup SNPs networks in the allele and dominant models were analysed, respectively. The minor allele of rs2228570 (FokI) and the minor allele of rs13181(ERCC2) was the first-ranking SNP in subgroup one and subgroup two in the allele model, respectively. In the dominant model, wildtype and heterozygous genotypes of rs475007 in subgroup one and mutated homozygous genotype of rs238406 in subgroup two were most likely to be associated with skin cancer, respectively. Conclusions: FokI rs2228570 and ERCC2 rs13181 in the alleles model and MMP1 rs475007 and ERCC2 rs238406 in the dominant model are closely linked to SC risk.